Investigating the operational behaviour of a double curvature arch dam - Prins, Zac James (Department of Civil Engineering, 2017)
The safety of dams is crucial in ensuring the continual availability of water, safety of the surrounding communities and infrastructure. Surveillance systems are implemented to monitor the structural integrity of certain dams which have a safety risk. The components and extent of the surveillance systems adopted depends on many factors, which include the type of dam wall structure used to impound the reservoir, geotechnical and environmental conditions. The case study used for this thesis is Kouga Dam located in the Eastern Cape Province of South Africa. It is a double curvature, concrete arch dam which supplies water for domestic, irrigation and industrial use to the Gamtoos River Valley and Nelson Mandela Metropolitan. During construction the stability of the right flank was questioned and subsequently, remedial measures were taken in order to increase the shear resistance of this flank. Previous dam safety evaluations also noted the possibility of Alkali Silica Reaction (ASR) occurring within the structure which resulted in concrete swelling and loss of strength. Due to these factors and the large hazard potential rating associated with this dam an intensive surveillance system has been used to monitor the dam's behaviour during operation. In this thesis the results of the surveillance system is analysed. A strong linear relationship exists between the temperature loading and displacement response of the dam wall. Changes in temperature initiate the response of the structure almost instantaneously. A more complex relationship exists between hydrostatic loading and the displacement response of the structure. A phase lag of approximately one to three months is evident between these two variables. Since construction the displacement and strain rates in the upstream (y) and upward (z) directions are 0.3mm/annum and 8.6με/annum respectively. However, since 1989 there has been a reduction in the average displacement and strain rates in all directions by approximately 70%. This may suggest that the ASR has stabilized. The vertical construction joints, especially the central and upper joints, are relatively open during low water levels. The structure is found to transfer the imposed loading mainly to the central foundation via dominant cantilever action. As a result the reaction forces on the upper foundation have been found to be relatively low, lowering the risk of potential shear failure of the right foundation. Small foundation movements of less than 0.3mm have been observed within the foundation downstream of the dam wall on the right flank. These movements are between 10 and 40m within the foundations.